2018
DOI: 10.1002/chem.201801565
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Hydrothermal Growth of Cobalt Spinel Water Oxidation Catalysts: From Preparative History to Catalytic Activity

Abstract: The hydrothermal growth of cobalt oxide spinel (Co O ) nanocrystals from cobalt acetate precursors was monitored with in situ powder X-ray diffraction (PXRD) in combination with ex situ electron microscopy and vibrational spectroscopy. Kinetic data from in situ PXRD monitoring were analyzed using Sharp-Hancock and Gualtieri approaches, which both clearly indicate a change of the growth mechanism for reaction temperatures above 185 °C. This mechanistic transition goes hand in hand with morphology changes that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 113 publications
0
16
0
1
Order By: Relevance
“…While Antonietti and Driess et al 41 tailored the particle size of cobalt oxides with related synthetic methods and found the efficiency of photo- and electrocatalytic water oxidation of Co 3 O 4 nanoparticles to depend on the available surface area, our previous studies on Co 3 O 4 hydrothermal growth mechanisms indicated that the surface area is not by all means the decisive performance parameter. 13…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Antonietti and Driess et al 41 tailored the particle size of cobalt oxides with related synthetic methods and found the efficiency of photo- and electrocatalytic water oxidation of Co 3 O 4 nanoparticles to depend on the available surface area, our previous studies on Co 3 O 4 hydrothermal growth mechanisms indicated that the surface area is not by all means the decisive performance parameter. 13…”
Section: Resultsmentioning
confidence: 99%
“…First, the predictivity of inorganic synthetic protocols is still limited, especially with respect to understanding the precise influence of diverse synthetic methods and conditions on crucial material parameters. 913 Consequently, establishing predictive preparation–properties–performance relations for WOCs remains a fundamental challenge. Moreover, recent results indicate that the key parameters required for optimal WOC performance can vary significantly with the applied catalytic test method.…”
Section: Introductionmentioning
confidence: 99%
“…Our work provided deeper insight into the control parameters of hydrothermal WOC formation processes, through a combination of mechanistic in situ and ex situ analytical methods. This comprehensive study provided guidelines about how the WOC performance of binary oxides can be improved through an empirical understanding of their growth mechanisms [58].…”
Section: Spinelsmentioning
confidence: 99%
“…In the case of Co 3 O 4 we recently demonstrated that the growth mechanism can play a key role in the resulting water oxidation activity (Reith et al, 2018). Therefore, we here started from a well-defined microwave protocol for microwave-assisted spinel-type Co 3 O 4 and systematically studied the influence of the synthetic parameters on the properties and catalytic performance of the emerging materials to demonstrate the importance of these parameters in microwave-hydrothermal WOC synthesis (Conrad et al, 2010(Conrad et al, , 2012(Conrad et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%